Labeling Nutrition-Sensitive Food Chains: A Consumer Preference Analysis of Milk Products - Wesana, Joshua; Gellynck, Xavier; Dora, Manoj K.; Muyama, Lucy; Mutenyo, Emma; Elizabeth, Ahikiriza; Kagambe, Edmond; De Steur, Hans (Frontiers in Nutrition, 2020)
While nutrition sensitive value chain approaches are strongly advocated, studies on consumer preferences for such interventions are lacking. This study aims to fill this gap by examining a nutrition sensitive chain labelling scheme, using the Ugandan dairy sector as a case. A survey was conducted among 250 consumers, primarily eliciting perceptions of the importance of a nutrition sensitive chain label compared to nutrition claims/facts. In addition, a choice-based conjoint experiment was designed with nutrition label, brand, fat content and price as attributes. Findings show that nutrition sensitive chain labelling was more positively perceived by consumers than nutrition claims/facts. Ordered logistic regression analysis indicated that BMI, nutrition knowledge and label use influenced consumers’ perceived importance of a nutrition sensitive chain label relative to sex, age, children and milk purchase frequency for nutrition claims/facts. This is confirmed by the higher utilities for the nutrition sensitive chain label in our conjoint experiment. Future research should focus on the integration of nutrition sensitive chain labelling with existing labels in a way that promotes candid interpretation by consumers. Industrial and policy actors in the agri-food sector can use these findings to innovate and regulate appropriate labelling schemes in the context of nutrition sensitive value chains.